Pulmonary sequestration associated with significant elevation of serum carbohydrate antigen 19-9: report of two cases - Ye, Xin; Fu, Yili; Hu, Bin; Li, Hui (Annals of Translational Medicine; Vol 4, No 19 (October 15, 2016): Annals of Translational Medicine, 2016)
This report presents two young women were admitted to the department of thoracic surgery, Beijng Chao-Yang Hospital because of the extremely elevation of the serum Carbohydrate antigen 19-9 (CA19-9). The enhanced Computed Tomography scan showed that the lesion of the lung and the anomalous artery, and diagnosis of the pulmonary sequestration was made. The positron emission tomography/computed tomography (PET/CT) scan was taken to exclude any kind of malignant tumor. Both of them had the lobectomy operation confirmed our preoperative diagnosis. After the operation, the serum level of CA19-9 decreased to normal range rapidly. Therefore, in these two cases, the markedly elevation of serum CA19-9 level may have resulted from the pulmonary sequestration.